Aplikasi WebGIS Hotel Di Kota Surakarta Memanfaatkan Google Maps API - Fajar Rusdyanto; Andri Suprayogi; Hani'ah . (Jurnal Geodesi UNDIP, 2014)
Technology development at this junction was already well that especially in the field of wireless networks. Began from a tool that’s used until to speed of the existing wireless network. The information that exist in an area could easily spread to another areas in just seconds. These things would very made light of communication in era that completely advance now. But the information that was exist if not managed properly will certainly could be difficult for the communication. So for that was  required a system that regulates the information or better known as information systems. Information systems are just written only and there are completely with pictures and maps. Information system that equipped with a map is called a Geographic Information System.In every city at this junction certainly equipped with luxurious accommodation facilities or better known by the hotel. One of the town are Surakarta which there are one of the tourist city. Information about this hotel are felt still not enough because hasn’t systems that organize them. Information systems were felt good enough to managed geographic information about the hotel is a geographic information system used the Internet or  Geographic Information System that based on web. By utilizing Google Maps felt good enough because it is a quite familiar in all operating system platforms that exist today. Geographic Information System technology are expected could helped to the users to obtained information on the spatial and non-spatial regarding hotels in the Surakarta city, Central Java .Keywords: Hotels, Surakarta,WebGIS